2012
DOI: 10.1063/1.3701562
|View full text |Cite
|
Sign up to set email alerts
|

Analytical evaluation of Fukui functions and real-space linear response function

Abstract: Many useful concepts developed within density functional theory provide much insight for the understanding and prediction of chemical reactivity, one of the main aims in the field of conceptual density functional theory. While approximate evaluations of such concepts exist, the analytical and efficient evaluation is, however, challenging, because such concepts are usually expressed in terms of functional derivatives with respect to the electron density, or partial derivatives with respect to the number of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 69 publications
(93 reference statements)
1
86
0
Order By: Relevance
“…We note that Yang et al 39 recently presented the theory for the analytic evaluation of this derivative. See Refs.…”
Section: Extension To Electron Densities: the Fukui Functionmentioning
confidence: 97%
“…We note that Yang et al 39 recently presented the theory for the analytic evaluation of this derivative. See Refs.…”
Section: Extension To Electron Densities: the Fukui Functionmentioning
confidence: 97%
“…[59]. Analytical expressions for second-order derivatives and linear response functions have very recently been proposed by Yang et al [60] The same authors also derived important constraints for the electronic structure that must be met by the exact exchange-correlation functional. In analogy to using constraints obtained for variable N e , such as piece-wise linear behavior and derivative discontinuities, to design improved density functionals, [61][62][63] A Cohen's current efforts are dedicated to variations in the external potentials that include fractional nuclear charges.…”
Section: Design Applicationsmentioning
confidence: 99%
“…3, the higher order effects mostly cancel, thereby rendering the first order HF derivative quite predictive. [59,60] To improve the predictive power of the first-order term in Eq. (9), an empirical correction has been introduced that ' 'linearizes' ' the energy through a global yet nonlinear Hamiltonian, [68] If we assume f ðkÞ to be a second-order polynomial in k, two coefficients are determined by the boundary conditions that Hðk ¼ 0Þ ¼ 0, and Hðk ¼ 1Þ ¼ 1, leaving one additional degree of freedom.…”
Section: Theorymentioning
confidence: 99%
“…Several authors suggested different approaches towards their calculation beyond finite differences 8,9 . In finite differences, the Fukui function is computed using the electron density of a molecule with N electrons and that with N ± δ electrons and the difference divided by δ is considered to be the Fukui function.…”
Section: Introductionmentioning
confidence: 99%